Essential Reading on Race and Law - Lindberg, Tracey (Labour / Le Travail, 2001)
The article reviews and comments on Constance Backhouse's "Colour-Coded Law: A Legal History of Racism in Canada 1900-1950," Sidney L. Harring's "The White Man's Law: Native People in Nineteenth-Century Canadian Jurisprudence,", and James W. St. G. Walker's "'Race,' Rights and the Law in the Supreme Court of Canada."